2017
DOI: 10.3727/154427217x15022104437756
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Dynamics Perspective on Adventure Tourism

Abstract: Traditional definitions for adventure tourism have focused on the adventure tourism activity or the adventure tourism environment. In these cases the activity is most often associated with risk and the environment associated with unfamiliarity and natural terrains. Critiques of these definitions have pointed out that this traditional perspective is limited. The risk focus is paradoxical as clients purchase adventure experiences involving risk and uncertainty, whereas tour operators must minimize the risk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 36 publications
0
30
0
2
Order By: Relevance
“…The motives for hard adventurers are seen as including risk and challenge (Lipscombe, 1995;Pomfret, 2006). However, it should be noted that recent studies have suggested moving beyond the hard-soft dichotomy (Cater, 2013;Peacock et al, 2017;Varley & Semple, 2015;Rantala, Rokenes & Valkonen, 2016). For example, Varley and Semple (2015) illustrate an example of slow adventure that involves a combination of low-difficulty and deep-end experience in the adventure.…”
Section: Soft and Hard Adventuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The motives for hard adventurers are seen as including risk and challenge (Lipscombe, 1995;Pomfret, 2006). However, it should be noted that recent studies have suggested moving beyond the hard-soft dichotomy (Cater, 2013;Peacock et al, 2017;Varley & Semple, 2015;Rantala, Rokenes & Valkonen, 2016). For example, Varley and Semple (2015) illustrate an example of slow adventure that involves a combination of low-difficulty and deep-end experience in the adventure.…”
Section: Soft and Hard Adventuresmentioning
confidence: 99%
“…Also Peacock et al (2017) point out that there is a paradox in that clients purchase adventure experiences involving risk and uncertainty, whereas tour operators must minimize the risk and emphasize safety. They emphasize that it is often forgotten that individuals undertake adventure for a variety of reasons, including risk and thrills, health and well-being, connection to others and nature, recreational mastery, and personal development.…”
Section: Soft and Hard Adventuresmentioning
confidence: 99%
“…Examples of such activities include kayaking, BASE (Building, Antennae, Space and Earth) jumping, skiing, climbing, walking and surfing. Additionally, the growth of adventure tourism and participation in nature sports has expanded possible participation beyond the wellresearched and established realms of outdoor education (Peacock, Brymer, Davids & Dillon, 2017). Consequently, we take a position that reflects a leisure, tourism and participation perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Adventure tourism has significantly created a research momentum in international literature over the last two decades (Peacock et al, 2017). This topic has raised both academics and practitioner's attention as they see the vast potential within this tourism market niche.…”
Section: Adventure Tourismmentioning
confidence: 99%
“…Adventure tourism is one of the fastest expanding niche or segments in the global tourism industry (Clinch et al, 2017;McKay, 2013;Peacock et al, 2017;World Tourism Organization, 2014). According to McKay (2013), adventure tourism is a style of tourism whereby travellers commence a physical activity that would hold as somewhat outside their comfort zone and where some risk to life and extremity is involved.…”
Section: Introductionmentioning
confidence: 99%